Almost Weak Continuity for Multifunctions Defined between an Ideal Topological Space and a Bitopological Space (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions, called upper almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions. Moreover, several characterizations and some properties concerning upper almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunctions are considered.
Keywords: upper almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunction; lower almost weakly $τ^\star(σ_1,σ_2)$-continuous multifunction